Radical Markets by Eric Posner and E. Glen Weyl: A Review Essay - Levine, David K. (Journal of Economic Literature, 2020)
At a time when standards of living have improved more than any time in history, this book makes a proposal for radical change. It is based—loosely—on market design principles. The plan for attacking overlapping ownership is reasonably well thought out. Most of the book, however, proposes to use mechanisms designed for a narrow purpose; to attack real or imagined problems that they are ill—suited to solve. I conclude that while market design has a lot to offer when properly applied, the proposals here are not sufficiently well thought out to constitute a serious plan of action.(JEL D44, D47, D72, D82, P14)